Analisis Pengaruh Tingkat Suku Bunga, Pengeluaran Pemerintah, Konsumsi Masyarakat, Jumlah Uang Beredar, serta Nilai Tukar Terhadap Inflasi di Indonesia Tahun 1997-2020 - Mahar Fatwa Nugroho; Yuni Prihadi Utomo (Ekonomis: Journal of Economics and Business, 2022)
Inflation is a decline in the purchasing power of money and is reflected in the general rise prices of goods and services in an economy. Inflation decrease real income and has a negative impact on macroeconomy. The purpose of the study is to determine the impact of interest rates, government spending, public consumption, money supply, and exchange rates on Indonesia inflation during the periode 1997-2020, using Ordinary Least Square reservation analysis. The outcomes display authorities spending and the exchange rate had a positive effect on inflation, and the money supply had a negative impact on inflation. On the order hand, between 1997 until 2020, interest rates and public consumption did not affect Indonesia’s inflation.